Ecotourism research progress: A bibliometric analysis (period 2002–2022) using VOSviewer Software - Le, Anh Toai; Nguyen, Hoang Son (Turyzm/Tourism, 2023)
This study aims to conduct a bibliometric analysis of ecotourism literature in the period from 2002 to 2022 using VOSviewer software. 1,693 articles indexed by Scopus were analyzed. The results reveal that ecotourism is a developing research field that attracts scholars from many countries. Most of the articles were published in the United States, China, Indonesia, Malaysia, Australia, and the United Kingdom. The study identified four main thematic areas: (a) the involvement of local communities and stakeholders in ecotourism management and development in protected areas; (b) ecotourists’ perceptions, attitudes and behaviours; (c) the use of technology and environmental management to support ecotourism development planning and management; and (d) biodiversity conservation and sustainable development in ecotourism. This study suggests that decision-making based on data, stakeholder participation and climate adaptation in the planning and management of ecotourism is attracting the attention of researchers worldwide.